2014
DOI: 10.1080/02827581.2014.982166
|View full text |Cite
|
Sign up to set email alerts
|

Economics of harvesting uneven-aged forest stands in Fennoscandia

Abstract: This study analyzes the optimal harvesting of uneven-aged Norway spruce (Picea abies (L.) Karst.), Scots pine (Pinus sylvestris L.), and birch (Betula pendula Roth. and B. pubescens Ehrh.) stands. The analysis is based on an economic description of uneven-aged forestry using a size-structured transition matrix model and a single-tree model. The optimization problem is solved in its general dynamic form using gradient-based interior point methods. Increasing the harvesting interval decreases the annual volume y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…This two parametric (α and β) log-logistic distribution accounted for the general rule that the number of recruits decreases with increasing stand density (Stancioiu & O'Hara 2006), but it also considered that recruitment is possible only at a minimum stand density representing continuous cover of mature stands with seed trees (Amm et al 2014). Such a function may be more realistic for shade tolerant species than commonly used functions for recruitment (Rämö & Tahvonen 2014), which assume a monotonous decrease of recruitment with increasing ba, implying that maximum recruitment occurs on bare land. Using a dispersal recruitment model, Amm et al (2014) showed that silver fir seed dispersal occurs at shorter distances from seed trees than previously thought, indicating that sufficient stand density should be maintained for successful recruitment (eqn.…”
Section: Matrix Transition Modelmentioning
confidence: 99%
“…This two parametric (α and β) log-logistic distribution accounted for the general rule that the number of recruits decreases with increasing stand density (Stancioiu & O'Hara 2006), but it also considered that recruitment is possible only at a minimum stand density representing continuous cover of mature stands with seed trees (Amm et al 2014). Such a function may be more realistic for shade tolerant species than commonly used functions for recruitment (Rämö & Tahvonen 2014), which assume a monotonous decrease of recruitment with increasing ba, implying that maximum recruitment occurs on bare land. Using a dispersal recruitment model, Amm et al (2014) showed that silver fir seed dispersal occurs at shorter distances from seed trees than previously thought, indicating that sufficient stand density should be maintained for successful recruitment (eqn.…”
Section: Matrix Transition Modelmentioning
confidence: 99%
“…Bollandsås et al (2008) use Norwegian National Forest Inventory data and estimate uneven-aged models for most common Nordic tree species. Their model can be expected to be suitable for all of Fennoscandia (Rämö and Tahvonen 2014). In our study, we use their results for Norway spruce.…”
Section: The Size-structured Optimization Problem For Varying Harvestmentioning
confidence: 99%
“…While optimal rotation models include a single tree cohort (with perhaps a heterogeneous size structure) and some finite rotation length that is repeated as identical, a general model for continuous cover management includes regeneration dynamics, multiple tree cohorts and size classes, and no obvious length for a finite time horizon. The research on CCF includes several suggestions for simplifying the analysis to an essentially static model with economically unclear objective functions (for discussion, see Getz and Haight (1989) and Rämö and Tahvonen (2014)). The understanding of how to optimize CCF is still far from complete in both research and practical operations.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the foresters soon reverted to clear-cutting, the 1869 plan initiated a discussion regarding the advantages and disadvantages of different logging methods. The discussion of clear-cutting versus selective cutting was ongoing then (Lundmark et al 2013) and still is very much so today (Rämö and Tahvonen 2014). Early discussions mostly focused on storm resistance and regeneration.…”
Section: Selective Cutting Versus Clear-cuttingmentioning
confidence: 99%
“…It was also based on the German tradition, but the Finnish foresters stressed that forest management should be adapted to a country's specific conditions rather than according to the models developed in other countries (von Berg 1859). Nevertheless, based on a description of the applied directives, the Finnish principles of forest management seemed to closely follow those applied in Germany, Denmark and Sweden (Michelsen 1999), and since 2014 the Finnish forest legislation also allows other alternatives than even-aged forest management (Rämö and Tahvonen 2014). Norway also has a long history of forestry but it was not until around 1900 that a more sustainable forest management was introduced (Aasetre and Bele 2009).…”
Section: Introductionmentioning
confidence: 99%